Improving the Cognitive Abilities of Grade III Students through the Application of the Teaching at the Right Level (TaRL) Approach in Science Subjects - Neng Vini Avionita; Mursidah Rahmah; Fajar Dwi Kurniawati; Ningrum Sri Indriani; Anita Karolina (Program Studi PGMI, 2026)
This study aims to improve the cognitive abilities of third-grade elementary school students through the implementation of the Teaching at the Right Level (TaRL) approach in the subject of Natural and Social Sciences (IPAS). The background of this research is the low cognitive achievement of students due to instructional strategies that are not aligned with their level of understanding. The research was conducted as a Classroom Action Research (CAR) using the Kemmis and McTaggart model over two cycles, involving 28 students at SDN Julang, Bogor City. Data were collected through observations and cognitive achievement tests, analyzed both quantitatively and qualitatively. The results showed a significant improvement in student learning outcomes. The percentage of students achieving mastery increased from 35.71% in the pre-cycle to 64.29% in the first cycle and reached 89.29% in the second cycle. The average score also increased from 61.07 (pre-cycle) to 77.86 (cycle II). The implementation of TaRL, supported by ability-based grouping, tiered LKPD, visual media, and interactive educational games through Wordwall, proved effective in creating a more contextual, enjoyable, and meaningful learning experience. Therefore, TaRL can be considered an adaptive and inclusive learning strategy to enhance cognitive development in IPAS learning at the elementary level.